THE EFFECTIVENESS OF WRITTEN CORRECTIVE FEEDBACK IN TEACHING WRITING CAUSE EFFECT AT THE ELEVENTH GRADE OF SMA NEGERI 1 GROGOL KEDIRI - Pamungkas, Ratna Dewi; Amroni, Agus (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2021)
This article aims to know the Effectiveness of Written Corrective Feedback in Teaching Writing Cause Effect at the Eleventh Grade of SMAN 1 Grogol Kediri. This research was quantitative experimental design, more specifically uses true experimental by posttest only controls class design to analyze the data. The data were analyzed and interpreted by means of SPSS 23.0 version. The study reveals that the effectiveness of written corrective feedback has a significant effect on students’ writing achievement in term of content of the text: content, organization, vocabulary, language use and mechanic. The result of students’ writing score from control class and experimental class demonstrated a significant difference. It is found that the experimental class outperformed the control class in writing achievement with t = 9.021, df = 66 and P = .000 and 95% Confidence Interval ranging from 9.138 to 14.332. From the sig. (2-tailed) we can see the P is lower than 5% (0.000 < 0.005). So, it can be concluded that the value is significant in 5% significant level. Thus, the significance different between the mean value of both class is found.